Mahathir Mohamad in Public Policy and Politics of Malaysia - Endi Haryono; Patrick Ziegenhain (Populasi, 2022)
This article deals with the political and social achievements, but also the shortcomings of Mahathir Mohamad as the long-term prime minister of Malaysia. Based on a thorough and critical literature review the authors discuss first Mahathir’s reaction to the financial crisis in 1997/98 and the upcoming reformasi movement. Then, they analyze the conditions for the re-emergence of Mahathir as opposition leader in the mid-2010s and his role in the surprising election victory of the Pakatan Harapan coalition in 2018. Mahathir, a charismatic leader in Malaysia during the 1980s and 1990s, has contributed an important role in the development and change of politics in Malaysia. The victory of the opposition coalition in the 2018 election would be hardly possible without him. His political comeback prior to the election made headlines in Malaysian media and raised high hopes for a more democratic Malaysia.